2017
DOI: 10.1016/j.pcd.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial barriers to healthcare use among individuals with diabetes mellitus: A systematic review

Abstract: We identified a broad range of barriers to healthcare use in individuals with diabetes mellitus. However, the number of studies is low. Further research is needed to analyse barriers in more detail considering special subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…In this study, nursing care plans for patients with chronic diseases were examined. It is known that chronic medical diseases cause many psychosocial problems for the patient . Although physiological nursing diagnoses were identified 15.77 ± 11.55, psychosocial nursing diagnoses were 3.05 ± 2.28.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, nursing care plans for patients with chronic diseases were examined. It is known that chronic medical diseases cause many psychosocial problems for the patient . Although physiological nursing diagnoses were identified 15.77 ± 11.55, psychosocial nursing diagnoses were 3.05 ± 2.28.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that chronic medical diseases cause many psychosocial problems for the patient. 18,19 Although physiological nursing diagnoses were identified 15.77 ± 11.55, psychosocial nursing diagnoses were 3.05 ± 2.28. It can be said that our students could easily determine physiological diagnoses but had difficulty in determining psychosocial diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that there are many barriers to primary healthcare services utilization among lower SES groups. These barriers can largely be divided into categories which are namely population characteristics, patients’ cultural norms and values as well as healthcare system related services [30]. One of the cultural reasons that may compromise utilization of primary healthcare services is the perceived superiority of alternative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Figure 2, qualitative analysis of the research revealed a link between patient knowledge enablers such as preconditions created by health technology (e-communities and accessibility of reliable information) [16,51,59,60,68,74] the patientcentered healthcare model [14,92] and all levels of patient empowerment.…”
Section: Proposition 1 Patient Empowerment Through Mediating Structumentioning
confidence: 99%